2011
DOI: 10.1177/030089161109700314
|View full text |Cite
|
Sign up to set email alerts
|

Impact of delayed radiotherapy on local control in node-negative breast cancer patients treated with breast-conserving surgery and adjuvant radiotherapy without chemotherapy

Abstract: Early radiotherapy within 6 weeks of breast-conserving surgery is associated with increased local control in patients with node-negative breast cancer not undergoing chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…The impact of the TI from surgery to adjuvant therapy (radiation or concurrent chemoradiation) has been studied mainly in breast, endometrial, and head and neck cancers [101112132223]. Several retrospective cohort studies have found that a longer TI is associated with poor oncological outcomes of these cancers [10111222]. Recently, a study in 308 endometrial cancer patients found that delay (≥9 weeks) in beginning adjuvant RT after hysterectomy was associated with poor survival outcomes [23].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of the TI from surgery to adjuvant therapy (radiation or concurrent chemoradiation) has been studied mainly in breast, endometrial, and head and neck cancers [101112132223]. Several retrospective cohort studies have found that a longer TI is associated with poor oncological outcomes of these cancers [10111222]. Recently, a study in 308 endometrial cancer patients found that delay (≥9 weeks) in beginning adjuvant RT after hysterectomy was associated with poor survival outcomes [23].…”
Section: Discussionmentioning
confidence: 99%
“…11 In addition, Kim et al and Pinnaro et al also gave insignficant result (p = 0.51, p = 0.27) respectively. 13,20 In contrary, Jobsen et al study concluded that there was significant difference in DMFS between delayed vs non delayed radiotherapy with HR 0.3 (0.2-0.5), p < 0.001. Jobsen et al suggest to start radiotherapy 36 days after surgery which might be lead to 40-70% relative survival benefit.…”
Section: Distant Metastasis-free Survivalmentioning
confidence: 94%
“…Fifteen article, Barbieri V et al, 6 Benchalal M et al, 7 Benk V et al, 8 Cefaro GA et al, 9 Corradini S et al, 10 Hebert-Croteau N et al, 11 Jobsen JJ et al, 12 Kim K et al, 13 Knauerhase H et al, 14 Seneviratne S et al, 15 Campos R et al, 16 Mikeljevic J et al, 17 Hershman DL et al, 18 Donato V et al, 19 Pinnaro P et al 20 were each appraised in groups by 2 authors using standardized validity criteria for prognostic research. Several aspects were critically reviewed comprising of its validity, importance, and applicability.…”
Section: Critical Appraisalmentioning
confidence: 99%
See 2 more Smart Citations